An Analysis of Organisational Role Stress Among the Extensionists in ICAR- Krishi Vigyan Kendras - Rohit, Jagriti; Singh, Premlata; Satyapriya,; Sangeetha , V.; Kumbhare, N. V. (Indian Journal of Extension Education, 2017)
Stress has become inevitable in today's competitive environment. Though moderate level of stress is said to be a motivator  but high level of stress has an adverse impact both on the individual as well on the organization's performance. The  present study attempts to examine the organizational role stress among the Extensionists working in the Krishi Vigyan  Kendras. Atotal sample size of 240 Extension professionals were selected by simple random sampling technique from the  four zones viz., Agricultural Technology Application Research Institute (ATARI) Zone I, Zone II, Zone IV and Zone VII.  The scale developed by Pareek (1983) was used with suitable modifications to study the organizational role stress.  Extensionists were significantly different on the various components of role stress and Inter Role Distance was given the  highest rank. The comparison among the zones showed that the zones were significantly different on the organizational  role stress and the components Inter Role Distance, Role Stagnation, Role Expectation Conflict, Role load and Role  Inadequacy also were significantly different. Further, comparison for each role stressor for extensionists based on their  gender showed significant difference in role stress experienced across the group.
Keywords: Extension professional; experience; gender; krishi vigyan kendra; organizational role stress